HCI for Children with Disabilities - Guerrero-Garcia, Josefina; González-Calleros, Juan Manuel; Muñoz-Arteaga, Jaime; Collazos, César A (Human–Computer Interaction Series, 2017)
In this work the authors present an HCI principle-based approach to develop applications to assist children with disabilities. Design knowledge related to developing complex solution for this audience is explained from an interaction design point of view.